2019
DOI: 10.1186/s12891-019-2846-z
|View full text |Cite
|
Sign up to set email alerts
|

Cervical proprioception and its relationship with neck pain intensity in subjects with cervical spondylosis

Abstract: Background Cervical proprioception is critical in the maintenance of posture and movements, so its assessment in different cervical conditions has gained importance in recent clinical practice. Studies reporting this assessment in subjects with cervical spondylosis (CS) have not previously been investigated. The goals of the study are (1) comparison of joint position error (JPE) in subjects with CS to healthy control group. (2) Correlation of neck pain intensity to cervical proprioception in pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
65
4
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 31 publications
10
65
4
4
Order By: Relevance
“…Similarly, other studies have revealed a significant greater error in patients with chronic idiopathic neck pain when compared with asymptomatic controls, despite the variability in methods used in these studies [68,[82][83][84][85][86][87]. Cervical proprioceptive errors in the patients with cervical spondylosis were also shown to be significantly larger than those of the healthy control group, indicating that the cervical proprioception in the cervical spondylosis was impaired [55]. A systematic review including 14 studies suggested that JPE was significantly higher in the neck pain group than in the control group [79].…”
Section: Jpe Testmentioning
confidence: 66%
See 1 more Smart Citation
“…Similarly, other studies have revealed a significant greater error in patients with chronic idiopathic neck pain when compared with asymptomatic controls, despite the variability in methods used in these studies [68,[82][83][84][85][86][87]. Cervical proprioceptive errors in the patients with cervical spondylosis were also shown to be significantly larger than those of the healthy control group, indicating that the cervical proprioception in the cervical spondylosis was impaired [55]. A systematic review including 14 studies suggested that JPE was significantly higher in the neck pain group than in the control group [79].…”
Section: Jpe Testmentioning
confidence: 66%
“…As mentioned above, muscle spindles densely packed in the deep neck muscles are the main source of proprioception afferents in the neck. These structural and functional changes in the cervical deep and superficial muscles can change the discharge of muscle spindles, which affects the afferent input and leads to alterations in proprioception [13,55]. The results suggest that the complexity and multifaceted nature of neck muscle impairment exists in people with chronic neck pain.…”
Section: Cervical Muscle Impairment In Chronic Neck Painmentioning
confidence: 93%
“…Considering that the application of Kinesio™ tape was improper, even though it was applied to the cervical muscles, it could have provided sensory feedback during neck movements, thereby decreasing mechanical irritation of soft tissues [ 34 36 ]. There may be another explanation: a strong relationship between neck pain intensity and cervical proprioception in participants with neck pain [ 37 ], considering that increased pain intensity impairs cervical proprioception and vice versa. As we evidenced, there was a decrease in pain intensity at the 7th-day follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…At a given point in time, approximately 14 % to 16 % of the adult population globally experience neck pain [2] and the mean lifetime prevalence is 48.5 % [2]. Neck pain is associated with impaired postural control, increased cervical joint position errors, forward head posture, decreased neck muscle strength, impaired neuromuscular sensitivity, and altered motor control in the cervical spine [3,4]. Studies show reduced neck muscle strength in chronic neck pain (CNP) [4].…”
Section: Introductionmentioning
confidence: 99%